Assessing the impact of virtual learning on family medicine trainees’ medical knowledge using progress tests: a retrospective cohort study (Canadian Medical Education Journal, 2025)
Background: Progress testing provides residents with an opportunity to identify strengths and weaknesses, encouraging self-directed learning. The University of Toronto’s Department of Family & Community Medicine administers the Family Medicine Mandatory Assessment of Progress (FM-MAP) biannually to track resident competency and medical knowledge. Our aim was to determine the impact of virtual learning on Family Medicine residents.Methods: We administered previous iterations of the FM-MAP to the virtual learning cohort and compared scores to those of the in-person cohort between October 2020 - Spring 2022.Results: There were no statistically significant differences between in-person and virtual cohorts of first- and second-year postgraduate family medicine trainees regarding their overall FM-MAP score. Second-year family medicine trainees outperformed first year trainees in both cohorts.Conclusion: The study found no significant effect on the scores of first- and second-year family medicine trainees caused by the shift to virtual learning, suggesting medical curricula can incorporate virtual learning without compromising trainee progress, offering flexibility in medical education. Future studies could explore its applicability across different residency programs and long-term effects on clinical performance.